Penggunaan Data Satelit NOAA-AVHRR Dalam Mengukur Ketinggian Suhu Bandar-bandar Utama Di Malaysia - Ibrahim, Ab. Latif; Masron, Tarmiji; Abdul Majid, Aziz; Mohd. Hassan, Aida Hayati; Abdullah @ Ishak, Nor Adina; P. Ramli, Mohd. Hilmi; Abd. Rahman, Mohd. Zulkarnain (Universiti Malaysia Sabah, 2005)
The development and urbanization process in Malaysia has changed the face the earth. Land fill with tress and vegetation was replaced with concrete buildings and paved roads, which have an impact on the rate of heat production and retention. This research was conducted to study the increasing temperature in major cities such as Kuala Lumpur, Penang, Kelantan and Johor Bahru. This study used the NOAA -AVlHRR satellite data because it covers wide areas such as the whole of Peninsular Malaysia. The split window technique was used to extract the temperature from the NOAAÂ·AVHRH data. This method saved money, time and transportation costs, and it is suitable for wide area study. A comparison between the NOAA-AVHRR temperature data with the actual data collected by the weather stations in the above mentioned cities, showed no significant differences at< 1"C. This means the accuracy of the NOAA-AVHRR can be trusted and accepted.